Rural Investment Climate in Indonesia - McCulloch, Neil (ISEAS Publishing, 2009)
It is a delight to see it published and available to a wide audience." - C. Peter Timmer, Visiting Professor, Program on Food Security and Environment, Stanford University; Non-Resident Fellow, Center for Global Development
Description based on online resource; title from PDF title page (publisher's Web site, viewed 22. Jun 2018)
Keywords: Investments -- Indonesia; Rural industries -- Indonesia